Mutagenic and nonmutagenic bypass of DNA lesions by Drosophila DNA polymerases dpoleta and dpoliota. - Ishikawa, T.; Uematsu, N.; Mizukoshi, T.; Iwai, S.; Iwasaki, H.; Masutani, C.; Hanaoka, F.; Ueda, R.; Ohmori, H.; Todo, T. (Journal of Biological Chemistry, 2001)
cDNA sequences were identified and isolated that encode Drosophila homologues of human Rad30A and Rad30B called drad30A and drad30B. Here we show that the C-terminal-truncated forms of the drad30A and drad30B gene products, designated dpoletaDeltaC and dpoliotaDeltaC, respectively, exhibit DNA polymerase activity. dpoletaDeltaC and dpoliotaDeltaC efficiently bypass a cis-syn-cyclobutane thymine-thymine (TT) dimer in a mostly error-free manner. dpoletaDeltaC shows limited ability to bypass a 6-4-photoproduct ((6-4)PP) at thymine-thymine (TT-(6-4)PP) or at thymine-cytosine (TC-(6-4)PP) in an error-prone manner. dpoliotaDeltaC scarcely bypasses these lesions. Thus, the fidelity of translesion synthesis depends on the identity of the lesion and on the polymerase. The human XPV gene product, hpoleta, bypasses cis-syn-cyclobutane thymine-thymine dimer efficiently in a mostly error-free manner but does not bypass TT-(6-4)PP, whereas Escherichia coli DNA polymerase V (UmuD'(2)C complex) bypasses both lesions, especially TT-(6-4)PP, in an error-prone manner (Tang, M., Pham, P., Shen, X., Taylor, J. S., O'Donnell, M., Woodgate, R., and Goodman, M. F. (2000) Nature 404, 1014-1018). Both dpoletaDeltaC and DNA polymerase V preferentially incorporate GA opposite TT-(6-4)PP. The chemical structure of the lesions and the similarity in the nucleotides incorporated suggest that structural information in the altered bases contribute to nucleotide selection during incorporation opposite these lesions by these polymerases.